Manipulating Ionic Behavior with Bifunctional Additives for Efficient Sky‐Blue Perovskite Light‐Emitting Diodes - Zhou, Wei; Shen, Yang; Cao, Long‐Xue; Lu, Yu; Tang, Ying‐Yi; Zhang, Kai; Ren, Hao; Xie, Feng‐Ming; Li, Yan‐Qing; Tang, Jian‐Xin (Advanced functional materials, 2023)
Perovskite Light‐emitting diodes (PeLEDs) have emerged as a promising technique for future high‐definition displays due to their outstanding electroluminescent characters. However, the development of blue PeLEDs toward practical applications is seriously hindered by their inferior performance, which mainly arises from the detrimental halide ionic behavior and thus severe nonradiative recombination in mixed‐halide blue perovskite materials. Herein, efficient sky‐blue PeLEDs featuring spectrally stable emission at 483 nm are realized by employing bifunctional passivators of Lewis‐base benzoic acid anions and alkali metal cations to simultaneously passivate the under‐coordinated lead atoms and suppress halide ion migration. A decent external quantum efficiency (EQE) of 16.58% and a maximum EQE of 18.65% are achieved, which is further boosted to 28.82% through the optical outcoupling enhancement. This work demonstrates unique insight into the generality and individuality of this category of benzoates and puts forward a feasible guidance in choosing appropriate additives for efficient perovskite materials. Defect passivation and the suppression of halide ion migration are simultaneously achieved in mixed‐halide perovskite materials via the incorporation of bifunctional additives containing Lewis‐base group and alkali metal ions. Efficient sky‐blue perovskite light‐emitting diodes achieve an external quantum efficiency of 16.58%, which is further boosted to 28.82% by the optical outcoupling enhancement.